Effectiveness of the “Live with health” program in the lifestyles of teachers at Colegio Union, Lurigancho - Chosica, 2017 - Ríos Odicio, Priscila (2019)
Objective of this work is to determine the effectiveness of the “Live with health” program in the lifestylesof the Colegio Union, Lurigancho - Chosica, 2017. Methodology of quantitative approach, preexperimental design and longitudinal cutting. The population was made up of 68 teachers according tonon-probabilistic sampling. The instrument used was the questionnaire on lifestyle (Alpha de Cronbach0.8), the educational program was developed in 16 sessions, during 4 months. The results show thatthe “Live with health” program was effective in the lifestyles of teachers according to the Willcoxon test(p = 0.000), specifically in the dimensions, of physical activity (p = 0.000), recreation (p = 0.000), selfcare(p = 0.000), sleep (p = 0.000) and trust in God (p = 0.000) respectively; however, regarding thefeeding dimension (p = 1,000) it was not effective. 88.2% of teachers have unhealthy practices beforethe program and after the intervention 100% have healthy lifestyles. Conclusions The educationalprogram “Live with health” was effective in the lifestyle of teachers, making teachers acquire healthypractices.